Ionic liquid infused starch-cellulose derivative based quasi-solid dye-sensitized solar cell: exploiting the rheological properties of natural polymers - Selvanathan V.; Yahya R.; Shahiduzzaman M.; Ruslan M.H.; Muhammad G.; Amin N.; Akhtaruzzaman M. (Springer Science and Business Media B.V., 2023)
Adhesives; Biopolymers; Cellulose; Cellulose derivatives; Crystallinity; Dimethylformamide; Electrochemical impedance spectroscopy; Gels; Ionic liquids; Ionic strength; Polyelectrolytes; Polymer solar cells; Starch; Chemically modified; Hydroxyethyl celluloses (HEC); Interfacial resistances; Polymer crystallinity; Polymer electrolyte; Recombination reactions; Rheological analysis; Rheological property; Dye-sensitized solar cells; Adhesives; Cellulose Derivatives; Crystallinity; Gels; Ionic Strength